2005
DOI: 10.1562/2004-11-29-ra-383
|View full text |Cite
|
Sign up to set email alerts
|

Photochemical behaviour of 6-methylpterin in Aqueous Solutions: Generation of Reactive Oxygen Species

Abstract: Pterins are a family of heterocyclic compounds present in a wide range of living systems that participate in relevant biological functions and are involved in different photobiological processes. 6-Methylpterin (MPT) was investigated for its efficiency of singlet-oxygen (1O2) production and quenching in aqueous solution. The quantum yields of 1O2 production (phi(delta)) was determined by measurements of the 1O2 luminescence in the near-infrared upon continuous excitation of the sensitizer. Values of phi(delta)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(19 citation statements)
references
References 0 publications
2
16
1
Order By: Relevance
“…We determined these p K a , and values of 8.6 ± 0.1, 8.0 ± 0.1, 8.47 ± 0.04 and 8.4 ± 0.1 were found for DPT, RPT, PA and MFA, respectively. These values are similar to those previously determined for other related pterin derivatives (3–6,23).…”
Section: Determination Of Pkasupporting
confidence: 90%
See 3 more Smart Citations
“…We determined these p K a , and values of 8.6 ± 0.1, 8.0 ± 0.1, 8.47 ± 0.04 and 8.4 ± 0.1 were found for DPT, RPT, PA and MFA, respectively. These values are similar to those previously determined for other related pterin derivatives (3–6,23).…”
Section: Determination Of Pkasupporting
confidence: 90%
“…The reported p K a values of the amide nitrogen (Fig. 1) of 6‐hydroxymethylpterin (HPT) and 6‐methylpterin (MPT) are 8.1 ± 0.1 (5) and 8.33 ± 0.06 (6), respectively. To the best of our knowledge, the corresponding p K a values of other compounds included in the present study have not been reported in the literature.…”
Section: Determination Of Pkamentioning
confidence: 99%
See 2 more Smart Citations
“…Andrés H. Thomas, Alberto L. Cappareli and coworkers examined the ability of 6‐methylpterin (MPT) to photogenerate and quench in aqueous solution (6). Quantum yields for generation of singlet oxygen were 0.10 ± 0.02 and 0.14 ± 0.02 in acidic and alkaline media, respectively.…”
Section: Historical Perspectivementioning
confidence: 99%